Based Solutions Of The Curved Stamp Problem For Elastic Environments (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In this article, the issue of the interaction of the stamp with the elastic half-plane based on a certain regularity of the geometric profile is considered, and the case of determining the displacement, deformation components, normal stresses on the border of the stamp, and stresses at the internal points of the half-plane for the case where the boundary conditions are given in displacements is presented.